2019
DOI: 10.1136/bmjopen-2018-026073
|View full text |Cite
|
Sign up to set email alerts
|

Paramedics’ experiences of administering fascia iliaca compartment block to patients in South Wales with suspected hip fracture at the scene of injury: results of focus groups

Abstract: ObjectivesTo explore paramedics’ experience of delivering fascia iliaca compartment block(FICB) to patients with suspected hip fracture at the scene of injury.DesignFocus groups within a randomised controlled trial.SettingParamedics based at ambulance stations in the catchment area of one Emergency Department in South Wales, recruited and trained in a feasibility study about an alternative to routine prehospital pain management for patients with suspected hip fracture.Participants11 paramedics.InterventionPara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…It can also be administered by paramedics at the scene of injury although evidence of effectiveness in this setting is lacking 19 29 30 58. The RAPID study has demonstrated that paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital 60. This study did not raise any concerns about the acceptability of FICB to patients and families for managing prehospital trauma.…”
Section: Discussionmentioning
confidence: 86%
“…It can also be administered by paramedics at the scene of injury although evidence of effectiveness in this setting is lacking 19 29 30 58. The RAPID study has demonstrated that paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital 60. This study did not raise any concerns about the acceptability of FICB to patients and families for managing prehospital trauma.…”
Section: Discussionmentioning
confidence: 86%
“…Four themes were identified from the focus groups with paramedics: ability and acceptability, patient safety and experience, training, and scope of the paramedic practice [69]. Three themes were identified from patient interviews: memories of receiving pain management and care from ambulance teams, experience of paramedic care, and ongoing hospital treatment and rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…7,15 FICB can be easily performed and has been used as a good solution for managing femur fracture pain in emergency departments. 16 Evans, et al 2 reported prehospital administration of FICB for patients with suspected fractures at the scene of trauma, using the landmark technique with good results. Hards, et al 17 in their systematic review concluded that FICB is appropriate technique for prehospital pain management, with a high success rate and few adverse effects.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…Additionally, patients reported inadequate analgesia for this severe painful fracture with up to 40% of patients did not receive any analgesics. 2,3 Poor pre-operative pain management in patients with femur bone fractures may be harmful, it can initiate physiological stress response which may lead to tachycardia, hypertension and arrythmias (may harm elderly and cardiac patients), an increase in the hemostatic system, deep venous thrombosis resulting from venous stasis, impaired immune system which result in increased infections, postoperative fatigue and delay in return of muscle function. 4 Disclosure: The authors have no financial interest to declare in relation to the content of this article.…”
Section: Introductionmentioning
confidence: 99%